Anti-Alpha-Amino-3-Hydroxy-5-Methyl-4-Isoxazolepropionic Acid Receptor Encephalitis: A Review - Zhang, Tian-Yi; Cai, Meng-Ting; Zheng, Yang; Lai, Qi-Lun; Shen, Chun-Hong; Qiao, Song; Zhang, Yin-Xi (Frontiers in Immunology, 2021)
Anti-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) encephalitis, a rare subtype of autoimmune encephalitis, was first reported by Lai et al in 2009. The AMPAR antibodies target against extracellular epitopes of the GluA1 or GluA2 subunits of the receptor. AMPARs are expressed throughout the central nervous system, especially in the hippocampus and other limbic regions. Anti-AMPAR encephalitis was more common in middle-aged women and most patients had an acute or subacute onset. Limbic encephalitis, a classic syndrome of anti-AMPAR encephalitis, was clinically characterized by a subacute disturbance of short-term memory loss, confusion, abnormal behavior and seizure. Magnetic resonance imaging often showed T2/fluid-attenuated inversion-recovery hyperintensities in the bilateral medial temporal lobe. For suspected patients, paired serum and cerebrospinal fluid (CSF) testing with cell-based assay were recommended. CSF specimen was preferred given its higher sensitivity. Most patients with anti-AMPAR encephalitis were complicated with tumors, such as thymoma, small cell lung cancer, breast cancer, and ovarian cancer. First-line treatments included high-dose steroids, intravenous immunoglobulin and plasma exchange. Second-line treatments, including rituximab and cyclophosphamide, can be initiated in patients who were non-reactive to first-line treatment. Most patients with anti-AMPAR encephalitis showed a partial neurologic response to immunotherapy.